Image-guided system endoscopic drainage of orbital abscess causedby methicillin-resistant Staphylococcus aureus in an infant - Tan, Chai-Lee; Nadarajah, Sanjeevan; Abdullah, Baharudin; Mohamad, Irfan; Maruthamuthu, Thevagi; Nadarajan, Chandran; Talib, Norain; Ismail, Shatriah (Elsevier, 2017)
INTRODUCTION: The management of orbital abscesses in neonates and infants is very challenging. Surgicaldrainage of the abscess is aimed at removing the pus and preventing blindness. We describe a case oforbital abscess in an infant that was caused by methicillin-resistant Staphylococcus aureus and that wassuccessfully drained with image-guided endoscopic surgery.PRESENTATION OF CASE: A 39-day-old infant presented with progressive right maxillary swelling com-plicated by methicillin-resistant Staphylococcus aureus orbital abscess. Tooth bud abscess was the mostlikely primary cause and a combination of intravenous antibiotics was initially prescribed. The collectionof intra-orbital pus was removed using image-guided system-aided endoscopic surgical drainage.DISCUSSION: Prompt diagnosis and management are very crucial. Endoscopic drainage of these abscessesin children has been described. Image-guided drainage of the orbital abscess is a newer technique thathas been reported in a teenager and in adult patients. This is the first reported case of endoscopic orbitaldrainage surgery in an infant. The procedure was performed successfully. This approach provides forbetter identification of the anatomical structures in a very young patient. Injuries to the medial rectus,globe and optic nerve can be avoided with this technique.CONCLUSION: Aggressive management of orbital abscesses in infants is mandatory. Image-guided endo-scopic orbital drainage offers precise visualization and a safer technique in a relatively smaller orbit.